Differences in the kinematics of the cervical and thoracic spine during functional movement in individuals with or without chronic neck pain: a systematic review. Issue 4 (December 2019) - Moghaddas, Diana; de Zoete, Rutger Marinus Johannes; Edwards, Suzi; Snodgrass, Suzanne J.
Abstract: Background: Chronic neck pain is common, impacting a person's ability to complete functional tasks. One method of quantifying functional movement is three dimensional (3D) motion analysis, however, it is unknown whether it may detect alterations in movement kinematics in individuals with neck pain. Objective: To systematically review studies to determine possible differences in cervical and thoracic kinematics during functional movement as measured by 3D motion analysis in individuals with neck pain compared to controls. Data sources: Medline, Amed, Scopus, Cochrane, Embase, CINAHL searched on 11/11/2017. Study selection: Studies reported 3D kinematics of functional movement (based on real-world situational biomechanics, i.e., multi-planar movements) of the cervical and thoracic spine in individuals with and without neck pain. Study appraisal and synthesis: Two reviewers assessed study quality; studies were summarised using discussion. Results: Four thousand four hundred and sixteen title/abstracts were screened, 11 full texts retrieved. Common reasons for exclusion were participants ≤8 years of age and studies that did not investigate functional movement. Included studies ( n = 5) used 3D motion analysis to assess kinematics during functional tasks including typing, gaming and resting posture. Participants with neck pain displayed greater neck flexion postures, reduced head velocity and smoothness of movement. Limitations: Variations in measurement methods and participant samples prevented meta-analysis. Conclusion: Though few studies were identified, altered kinematics were observed in individuals with neck pain, suggesting further research examining cervical spine kinematics is warranted. Recognising kinematic differences is important for clinicians to identify possible movement risk factors in individuals with neck pain that may be targeted with treatment. Systematic review registration number PROSPERO: CRD42017076053.